Zapisz w jak najprostszej postaci:

3b + (b + 1) =


8n – 3 + ( - 5n + 7) =


8 – 3y – ( - 7y2 - y + 5) =


7a – (a + b + ab) + (2a – 3ab) =


-2(4 – 3s + 5t) =


x(2x2 – x + 7) =


4(3 – 2m) + 5(3m + 6) =


-2(4t2 – 3t) – 3t(t – 2) =


(8n2 – 10n – 6) : (-2) =


+ 3x – 10 =


PROSZE POTRZEBUJE NA JUŻ!!!


Odpowiedź :

Odpowiedź:

3b + (b + 1) = 3b + b + 1 = 4b + 1

8n – 3 + ( - 5n + 7) = 8n - 3 - 5n + 7 = 3n + 4

8 – 3y – ( - 7y2 - y + 5) = 8 - 3y + 7y² + y - 5 = 7y² - 2y + 3

7a – (a + b + ab) + (2a – 3ab) = 7a - a - b - ab + 2a - 3ab = 8a - 4ab - b

-2(4 – 3s + 5t) = -8 + 6s - 10t

x(2x2 – x + 7) = 2x³ - x² + 7x

4(3 – 2m) + 5(3m + 6) = 21 - 8m + 15m + 30 = 7m + 51

-2(4t2 – 3t) – 3t(t – 2) = -8t² + 6t - 3t² + 6t = -11t² + 12t

(8n2 – 10n – 6) : (-2) = -4n² + 5n + 3

+ 3x – 10 = 3x - 10

Szczegółowe wyjaśnienie: